Starch-based nanocomposites for gene delivery - Abu, Tariq; Showkat, Ahmad Bhawani; Mehvish, Nisar; Mohd Razip, Asaruddin; Khalid M., Alotaibi (Woodhead Publishing, 2021)
Polysaccharide nanocomposites have drawn attention for their peculiar property of being renewable and green alternatives. Starch is a naturally renewable polymer having great potential owing to properties such as total compostability, biocompatibility, biodegradability, and are without toxic residues, besides few limitations including low mechanical properties, high water sensitivity, and poor processability. However, insertion of nanofillers into starch nanocomposites results in substantial changes and improvements in the stability and applicability of starch-based nanocomposites. This chapter aims to provide the fundamental knowledge on the role of starch nanocomposite polysaccharides, as specific in the field of biomedical applications, especially in gene delivery, as well as recent developments in this area.